Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2025)
Editorial (October-December, 2025) Global agriculture in 2025 is grappling with interconnected crises driven by conflict, climate change, and economic instability, leading to worsening food insecurity worldwide. On one side, farmers’ alliances are voicing concerns over proposed reforms to seed treaties that could threaten their rights, whereas scientists are presenting new evidence that a major overhaul of global food systems is essential to avoid climate disaster and improve health outcomes. Efforts are underway to reform agricultural policies to support farmers and ensure greater resilience against future biotic and abiotic shocks. The experiences gained through Viksit Krishi Sankalp Abhiyan, India, provided many insights in the form of demand for innovation, importance of localized knowledge, need for continuous outreach to bridge the research-practice gap, and a holistic approach to agriculture have to go a long way in designing sustainable agricultural framework. The current issue (October-December 2025) contains six research tools, seven research notes, and twenty-five full-length research papers. The diversity of full length papers focused on; Barriers to handicraft development in rural Saravan, Iran ;Utilization of smartphones for accessing agricultural information by farmers; Disruptions in Lifestyle Due to Escalating Screen Time; A Cross-state analysis of livelihood security among farm women; mapping dairy farmers’ preferences for improved feeding practices ; Farmers’ livelihood security through sheep farming; Exploring the dimensions of millet awareness among generational cohorts; Exploring consumer behaviour towards zero-sugar beverages; Bibliometric exploration of bullying; Influence of private extension services on practices and perceptions of shrimp farmers; ICT training directions in coastal Odisha; Factors influencing the adaptation behaviour of rice growers to climate change; Adoption and compliance of AI-enabled pest advisories; Crew position-based assessment of fishermen’s knowledge needs; Behavioural determinants of secondary agriculture-based entrepreneurs; Determinants of consumer perceptions towards value-added millet products; Determining the knowledge level and accessibility of major ICT tools; Modeling of farmers’ preferences towards climate-smart agriculture; Impact assessment of floating and alternative feeds for fish rearing technologies ;Influence of livelihood assets on agrochemical vs organic input use; Time management and procrastination patterns among undergraduate agriculture students; Communication and marketing behaviour of tomato growers; Modelling livelihood security of tribal farmers ; Use of generative AI by small-scale farmers in Nigeria; and Economic perspective of trends and determinants of paddy stubble burning. Among the Research Tools, Livelihood vulnerability of climate-sensitive farming communities, Attitude towards digital technologies in agriculture, Knowledge test on tick infestation in small ruminants, Farmers’ perception of capacity needs under NICRA, Knowledge test on scientific walnut cultivation, and Vegetable growers’ attitude towards safety measures in pesticide application were included. Research Note section has been enriched with the studies on Determinants of ARYA adoption for livelihood security, Constraints in the adoption of stress tolerant rice varieties, Perceived constraints among dairy farmers, Constraints in adopting improved chickpea cultivation practices, Perceived benefits and pre-design environmental impact assessment of eco-friendly ornament development, Constraints faced by farmers in adapting to climate change and constraints to digital literacy among joint liability groups. The Scopus cite score during the quarter increased from 1.4 to 1.7 (https://www.scopus.com/sourceid/21100846015). I, on behalf of the editorial board, extend my sincere thanks to all those who directly or indirectly assisted the editorial board. We acknowledge the contribution made by the reviewers by including their names. We acknowledge Ms. ACS publisher for maintaining the timeline. All the expert members of the editorial board and willing contributors are sincerely acknowledged. The support extended by the Executive Council is duly acknowledged. Special thanks are extended to Dr. U.S. Gautam, Dr. Satyapriya, Dr. Keshava, Dr. Basvaprabhu Jirli, and Dr. Bhanu P. Mishra for their insightful thoughts and guidance. (Manjeet Singh Nain)